The planning and implementation of complete streets in Quezon City translating legal framework into action - Marcall, Anna Clara Da Costa (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
Complete Streets are multimodal roads that are planned, designed, built and operated to be safe for all kinds of users.They increase travel options, flexibility, and usability, and they are of vital importance for sustainable development. The need for cleaner and more efficient urban mobility in Metro Manila has been recognized, and an extensive set of legal framework on sustainable transport is available. Given the potential of Complete Streets to enhance urban mobility and support economic and environmental sustainability, this research investigates why Complete Streets are not a rule rather than an exception in Metro Manila. Thus, the study assess the level of compliance of one of Metro Manila's LGUs (Quezon City) with Complete Streets concept, analyzing the content of its legal framework, as well as the planning and implementation of Complete Streets in the city. Moreover, the study seeks for reasons for the existing level of compliance, based on the institutional environment of the LGU. Finally, the completeness of one local road is evaluated based on its design and subjective assessments form street users. An important outcome of the research is the development of a methodology that can be applied to different municipalities and cities in the Philippines and abroad for the assessment of Complete Streets in terms of legal framework, planning and implementation.The results show a poor compliance of the local legal framework's content with Complete Streets concept, and low levels of planning and implementation of Complete Streets in the city. The road assessed was found not to be a Complete Street, and accordingly, it is not perceived as such by its users. Among the reasons for the low observance of Complete Streets principles, he most pressing are the prioritization of private motorized vehicles by the planning practices adopted, and culture and transportation habits of the population. Recommendations for enhancing the planning and implementation of Complete Streets in Quezon City include the adoption of a nationwide and/or metropolitan-wide Complete Streets policy; the rewriting of local policies to embrace Complete Streets; procedures and processes changes in the LGU; and the promotion of cultural changes. This research may provide policymakers and planners with a better understanding and basis on which to pursue street (re)design to create a safe, convenient and desirable network that accommodates all users.